Neuromyelitis optica spectrum disorders: long-term safety and efficacy of rituximab in Caucasian patients. (April 2016) - Radaelli, M; Moiola, L; Sangalli, F; Esposito, F; Barcella, V; Ferrè, L; Rodegher, M; Colombo, B; Fazio, R; Martinelli, V; Comi, G
Objective: To assess the long-term benefit-risk profile of repeated courses of rituximab in Caucasian patients affected by neuromyelitis optica (NMO) and related disorders, in everyday clinical practice. Methods: This is a prospective observational study performed at San Raffaele Hospital, Milan, Italy. From February 2006, we recruited 21 patients affected by NMO and NMO spectrum of disorders (NMOSD) whom underwent at least one cycle of intravenous (i.v.) rituximab and then were followed for at least 2 years. Results: At a mean follow-up time of 48 months, we observed a significant reduction of the annualized relapse rate (ARR), from 2.0 to 0.16 ( p < 0.01); and of the median Expanded Disability Status Scale (EDSS), from 5.5 to 4.0 ( p < 0.013). There were 12 patients (57%) who remained disease free during the follow-up period. Five patients (24%) reported mild hematological adverse events. Serious infectious adverse events were reported by another four patients: These were all wheelchair bound at the beginning of their rituximab treatment. Conclusions: A fixed treatment scheme of rituximab, with re-treatment every 6 months, was efficacious for NMO and NMOSD, with a good safety profile; however, to obtain an even better benefit-risk ratio, close monitoring of CD19 + B cells should be performed before the re-treatment of patients with high-level disability, concomitant leukopenia and hypogammaglobulinemia.